A Portable Magnetofluidic Platform for Detecting Sexually Transmitted Infections and Antimicrobial Susceptibility - Trick, Alexander Y.; Melendez, Johan H.; Onzia, Annet; Zawedde, Aidah; Nakku-Joloba, Edith; Kyambadde, Peter; Mande, Emmanuel; Matovu, Joshua; Atuheirwe, Maxine; Kwizera, Richard (Science translational medicine, 2021)
Effective treatment of sexually transmitted infections (STIs) is limited by diagnostics that cannot deliver results rapidly while the patient is still in the clinic. The gold standard methods for identification of STIs are nucleic acid amplification tests (NAATs), which are too expensive for widespread use and have lengthy turnaround times. To address the need for fast and affordable diagnostics, we have developed a portable, rapid, on-cartridge magnetofluidic purification and testing (PROMPT) polymerase chain reaction (PCR) test. We show that it can detect Neisseria gonorrhoeae, the pathogen causing gonorrhea, with simultaneous genotyping of the pathogen for resistance to the antimicrobial drug ciprofloxacin in <15 min. The duplex test was integrated into a low-cost thermoplastic cartridge with automated processing of penile swab samples from patients using magnetic beads. A compact instrument conducted DNA extraction, PCR, and analysis of results while relaying data to the user via a smartphone app. This platform was tested on penile swab samples from sexual health clinics in Baltimore, MD, USA (n = 66) and Kampala, Uganda (n = 151) with an overall sensitivity and specificity of 97.7% (95% CI, 94.7 to 100%) and 97.6% (95% CI, 94.1 to 100%), respectively, for N. gonorrhoeae detection and 100% concordance with culture results for ciprofloxacin resistance. This study paves the way for delivering accessible PCR diagnostics for rapidly detecting STIs at the point of care, helping to guide treatment decisions and combat the rise of antimicrobial resistant pathogens.